2017
DOI: 10.1002/2016rs006191
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor estimation using digital terrestrial broadcasting waves

Abstract: A method of estimating water vapor (propagation delay due to water vapor) using digital terrestrial broadcasting waves is proposed. Our target is to improve the accuracy of numerical weather forecast for severe weather phenomena such as localized heavy rainstorms in urban areas through data assimilation. In this method, we estimate water vapor near a ground surface from the propagation delay of digital terrestrial broadcasting waves. A real‐time delay measurement system with a software‐defined radio technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The authors have been developing a method of water vapor measurements near the surface with propagation delay of digital terrestrial broadcasting wave due to water vapor (Kawamura et al, 2017). The basic idea of using propagation delay is the same as that of retrieving PWV using GNSS.…”
Section: A System For Synchronized Multi-radar Scanning For Meteorolomentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have been developing a method of water vapor measurements near the surface with propagation delay of digital terrestrial broadcasting wave due to water vapor (Kawamura et al, 2017). The basic idea of using propagation delay is the same as that of retrieving PWV using GNSS.…”
Section: A System For Synchronized Multi-radar Scanning For Meteorolomentioning
confidence: 99%
“…Results show that the analysed algorithms are strongly dependent on the radar site and must be necessarily customized to each radar location, because the ground and sea clutter signatures are strongly dependent on the height above and proximity to the sea, surrounding orography etc. Our previous research presented that excellent sidelobe reduction capability in phased array digital beam forming is realized by minimum mean square error (MMSE) approach (Yoshikawa et al, 2013). This work applied the MMSE approach to Doppler spectral processing that is governed by the same equation as phased array digital beam forming.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The phase changes are estimated by the phase-locked loop (PLL) or by some another phase estimation technique. Kawamura et al (2017) found that the propagation delay of digital terrestrial broadcasting waves can be related to the content of water vapour in the respective volume of the atmosphere. They measured the time delay of the reflected signal between the receiver and the reflector in the form of the phase delay which is obtained as a phase in the maximum of the side lobe magnitude of the complex time-lag (power delay) profile.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, advanced vehicles that store these data can, in essence, be used as moving rain gauges (Rabiei et al, 2013). Kawamura et al (2017) have revealed a novel technique for monitoring atmospheric humidity using terrestrial broadcasting waves, based on propagation delays due to water vapor. Data shared as open source from social networks have been found to be potentially effective in improving automatic weather observations.…”
mentioning
confidence: 99%